Analysis of the dynamic mechanical property of multiple direction impact protection structure inspired by C60 molecule. (September 2019) - Shen, Xinhui; Liu, Jinguo; Zhang, Pengwei; Ni, Zhiyu; Liu, Yuwang
The natural structures have excellent dynamic mechanical properties. In this work, an impact protection structure inspired by the C60 molecule was proposed. And a model of a hollow ball protected by the bio-inspired C60 molecular structure during a drop testing was built. For the bio-inspired C60 molecular structure, the drop process and the dynamic mechanical property was investigated by LS-DYNA software. The results indicate that the bio-inspired C60 molecular structure has a good ability to protect against impact. Furthermore, the effects of the diameter ratio, materials, drop height, and angle were discussed. These variations of geometry and material can influence the dynamic mechanical properties of the bio-inspired C60 molecular impact protection structure.